2021
DOI: 10.1108/jcom-11-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

Internal crisis communication and the social construction of emotion: university leaders' sensegiving discourse during the COVID-19 pandemic

Abstract: PurposeThe paper explores university leaders' employee-focused sensegiving discourse during the COVID-19 health crisis. The aim is to reveal how leadership sensegiving narratives construct emotion in the rhetor-audience relationship.Design/methodology/approachA social constructionist, sensemaking approach centres on the meaning-making discourse of university leaders. Using rhetorical discourse analysis (RDA), the study analysed 67 emails sent to staff during a three-month period at the start of the global pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
13
0
4
Order By: Relevance
“…Analyzing responses from nearly 500 full-time U.S. employees during April 2020, Li et al (2021) showed how transparent internal communication reduced employees’ change-related uncertainty, aided their ability to cope with the associated stress, and improved organization-employee relationships. Internal organizational crisis communication in the form of sense-giving and meaning-making discourse by leaders in two U.K. universities helped employees make sense of the implications of the COVID-19 health crisis ( Yeomans & Bowman, 2021 ). Such communication involved core narratives of organizational resilience and competence; empathy, reassurance, and recognition; and aspects of location and community.…”
Section: Review and Hypothesesmentioning
confidence: 99%
“…Analyzing responses from nearly 500 full-time U.S. employees during April 2020, Li et al (2021) showed how transparent internal communication reduced employees’ change-related uncertainty, aided their ability to cope with the associated stress, and improved organization-employee relationships. Internal organizational crisis communication in the form of sense-giving and meaning-making discourse by leaders in two U.K. universities helped employees make sense of the implications of the COVID-19 health crisis ( Yeomans & Bowman, 2021 ). Such communication involved core narratives of organizational resilience and competence; empathy, reassurance, and recognition; and aspects of location and community.…”
Section: Review and Hypothesesmentioning
confidence: 99%
“…, 2019; Li et al. , 2021; Yeomans and Bowman, 2021), broader findings on job frustration and employees' self-protective mechanism of job disengagement are scarce. Particularly, the study of employees' job disengagement as a separate construct is important, as an employee's withdrawal from his/her work role goes beyond a mere absence of employee engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Esses fatos trazem a oportunidade de estudar o sensemaking dentro de um contexto extremamente difícil, novo e em rápida mudança (Yeomans & Bowman, 2021). Nesse cenário imprevisível e avassalador, a construção de sentido é mais complexa.…”
Section: Sensemaking Durante a Pandemiaunclassified
“…No campo dos estudos organizacionais, as pesquisas sobre sensemaking examinam como acontece a construção de sentido e seu impacto nos principais momentos vividos nas organizações. Abordam, por exemplo, as situações vividas pelas pessoas nos momentos de tomada de decisões, mudanças estratégicas, projetos de inovação e de aprendizagem organizacional, dentre outras (Brown, Colville & Pye, 2014;Maitlis & Christianson, 2014;Yeomans & Bowman, 2021).…”
unclassified